Outcomes Assessment of Lunate Replacement Arthroplasty with Intrinsic Carpal Ligament Reconstruction in Kienböck's Disease. (September 2014) - Henry, Mark
Background: With advanced Kienböck's disease, hyaline cartilage delamination or bone fragmentation render the lunate unsalvageable. Common surgical options are proximal row carpectomy, scaphotrapeziotrapezoid fusion, scaphocapitate fusion, or total wrist fusion. The purpose of this study was to prospectively evaluate the clinical and radiographic outcomes of one alternative: lunate prosthetic replacement arthroplasty combined with reconstruction of the scapholunate and lunotriquetral interosseous ligaments using the flexor carpi radialis tendon. Methods: Eligible patients with advanced Kienböck's disease and an unsalvageable lunate were included in this prospective study on a self-selected basis, forming a study group of 13 consecutive patients, 6 males and 7 females with a mean age of 40. Clinical and radiographic measurements were compared at a mean follow-up of 30.3 months from surgery with a paired, single-tailed, Student's t test using a p value of 0.05 as statistically significant. Results: Mean preoperative/postoperative clinical measurements were as follows: wrist flexion 29.2°/43.3°, wrist extension 24.2°/53.3°, absolute value grip strength 12.3/31.5 kg, grip strength vs. contralateral 36.5/85.2 %, and DASH scores 39.1/7.7. Mean initial/immediate postoperative/final ***radiographic measurements were the following: scapholunate angle 64.2°/46.7°/46.4°, radioscaphoid angle 64.6°/42.1°/45°, and modified carpal height ratio 1.20/1.62/1.59. Preoperative to postoperative differences were all statistically significant. Conclusions: Although these subjective and objective results reflect substantial improvement, there remain recognizable deficiencies in both prosthetic design and surgical strategy that require further modification.